The influence of vitamin E-coated dialysis membrane on oxidative stress during a single session of on-line hemodiafiltration - Antić, Svetlana; Draginić, Nevena; Pilčević, Dejan; Živković, Vladimir; Srejović, Ivan; Jeremić, Nevena; Petrović, Dejan; Jakovljević, Vladimir (Vojnosanitetski pregled, 2021)
Background/Aim. Oxidative stress is an important risk factor for the development of cardiovascular atherosclerotic diseases in the population of patients treated with regular hemodialysis. Bioincompatibility of the dialysis membrane and increased concentration of endotoxin in the hemodialysis solution are two main factors that can trigger oxidative stress. This paper was intended to examine the effect of a vitamin E-coated membrane on oxidative stress during a single session of on-line hemodiafiltration. Methods. Twenty-four patients undergoing hemodiafiltration with vitamin E-coated polysulfone dialysis membrane (Leoceed 21H) were examined, followed by a polysulfone dialysis membrane treatment without vitamin E (FX800). The following parameters of oxidative stress were measured: superoxide anion radical (O2-), hydrogen peroxide (H2O2), thiobarbutyric acid reactive substances (TBARS), nitric oxide (NO2-), catalase (CAT), superoxide dizmutase (SOD), and reduced glutathione (GSH) activity. Statistical analysis included the Kolmogorov-Smirnov test, Student-t test and Wilcoxon test. Results. On-line hemodiafiltration using a high-flux polysulfone vitamin E-coated membrane led to significant reduction of TBARS concentration and SOD activity, while the on-line hemodiafiltration session using a high-flux polysulfone membrane that is not vitamin E-coated induced a significant increase in H2O2 concentration in the serum and a decrease in SOD activity. There was no statistical significance among the other parameters of oxidative stress. Conclusion. A single session of on-line hemodiafiltration using a vitamin E-coated polysulfone membrane significantly affects oxidative stress. After a single session of on-line hemodiafiltration using a vitamin E-coated membrane, the concentration of TBARS has significantly decreased. The decreased activity of superoxide dismutase could be a consequence of an increased loss of microelements during an on-line hemodiafiltration session using a high-flux polysulfone membrane. Patient selection, continuous on-line hemodiafiltration using a vitamin E-coated polysulfone membrane over a 3–6 month period and increased antioxidant protection capacity could possibly reduce the risk of cardiovascular morbidity and mortality in patients treated by hemodialysis.
Keywords: hemodiafiltration; membranes, artificial; oxidative stress; vitamin e